Developing Interactive Learning Multimedia for Mathematics Subject in Junior High School Grade VIII Student East Lombok - Samsul Lutfi; Kholida Ismatullah; Yosi Nur Kholiso (CV. Literasi Indonesia, 2021)
This study aims to: (1) produce interactive multimedia products for Mathematics Subject in SMP Grade VIII students (2) find out the quality of the product. This research was a research and development approach (R & D) by adapting Alessi and Trollip development model that is planning, design, and development. The validation process for the product is done by the alpha test stage, beta test, and product trial. The results of the research show that: (1) the developed product is interactive learning multimedia on mathematics subjects in the form of application with * .swf format. and * .exe, (2) Interactive learning multimedia developed is feasible to be used as a supporter of learning with an average score of 3.31 from media experts with the category of “good”, 3.6 from material experts with the category of